Further Evidence that Inhibition of Neuronal Voltage-Gated Calcium Channels Contributes to the Hypnotic Effect of Neurosteroid Analogue, 3β-OH - Timic Stamenic, Tamara; Manzella, Francesca M.; Maksimovic, Stefan; Krishnan, Kathiresan; Covey, Douglas F.; Jevtovic-Todorovic, Vesna; Todorovic, Slobodan M. (Frontiers in Pharmacology, 2022)
We recently reported that a neurosteroid analogue with T-channel-blocking properties, (3β,5β,17β)-3-hydroxyandrostane-17-carbonitrile (3β-OH), induced hypnosis in rat pups without triggering neuronal apoptosis. Furthermore, we found that the inhibition of the CaV3.1 isoform of T-channels contributes to the hypnotic properties of 3β-OH in adult mice. However, the specific mechanisms underlying the role of other subtypes of voltage-gated calcium channels in thalamocortical excitability and oscillations in vivo during 3β-OH-induced hypnosis are largely unknown. Here, we used patch-clamp recordings from acute brain slices, in vivo electroencephalogram (EEG) recordings, and mouse genetics with wild-type (WT) and CaV2.3 knock-out (KO) mice to further investigate the molecular mechanisms of neurosteroid-induced hypnosis. Our voltage-clamp recordings showed that 3β-OH inhibited recombinant CaV2.3 currents. In subsequent current-clamp recordings in thalamic slices ex vivo, we found that selective CaV2.3 channel blocker (SNX-482) inhibited stimulated tonic firing and increased the threshold for rebound burst firing in WT animals. Additionally, in thalamic slices we found that 3β-OH inhibited spike-firing more profoundly in WT than in mutant mice. Furthermore, 3β-OH reduced bursting frequencies in WT but not mutant animals. In ensuing in vivo experiments, we found that intra-peritoneal injections of 3β-OH were less effective in inducing LORR in the mutant mice than in the WT mice, with expected sex differences. Furthermore, the reduction in total α, β, and low  EEG power was more profound in WT than in CaV2.3 KO females over time, while at 60 minutes after injections of 3β-OH, the increase in relative β power was higher in mutant females. In addition, 3β-OH depressed EEG power more strongly in the male WT than in the mutant mice and significantly increased the relative δ power oscillations in WT male mice in comparison to the mutant male animals. Our results demonstrate for the first time the importance of the CaV2.3 subtype of voltage-gated calcium channels in thalamocortical excitability and the oscillations that underlie neurosteroid-induced hypnosis.